Raman spectroscopy of synthetic, geological and biological vaterite: A Raman spectroscopic study - Wehrmeister, U. (2010)
Raman spectroscopy was used to study vaterite samples of biological, geological and synthetic origin. The Raman band positions and the full width at half‐maximum (FWHM) of the lattice modes and the internal modes of the carbonate ion of all specimens show no significant differences between vaterites of different origin. With increasing Mg concentrations, synthetic vaterite samples show increasing FWHM in the region of the lattice modes and the three ν1 bands, whereas no change in luminescence was detected. In contrast, in situ measurements of vaterite areas in freshwater cultured pearls (FWCPs) by laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS) together with the Raman spectra obtained at the same points show that the luminescence intensity in biological samples is affected by the magnesium content. The Raman spectroscopic features of vaterite and parisite‐(Ce) are compared, and their similarities suggest that the structure of vaterite contains at least three crystallographically independent carbonate groups and similar carbonate group layers. A band at 263 cm−1 is observed for the first time in this study, whereas it could be demonstrated that bands previously reported at 130 and 190 cm−1 do not belong to vaterite.